Heat shock protein 90 inhibitor RGRN-305 potently attenuates skin inflammation - Ben Abdallah, Hakim; Seeler, Sabine; Bregnhøj, Anne; Ghatnekar, Gautam; Kristensen, Lasse S.; Iversen, Lars; Johansen, Claus (Frontiers in Immunology, 2023)
Chronic inflammatory skin diseases may have a profound negative impact on the quality of life. Current treatment options may be inadequate, offering an unsatisfactory response or side effects. Therefore, ongoing efforts exist to identify novel effective and safe treatments. Recent studies indicate that heat shock protein (HSP) 90 may be an oral treatment for psoriasis. In this study, we discovered that HSP90 inhibition robustly suppressed 12-O-tetradecanoyl-phorbolester-12-acetate (TPA)-induced inflammation by targeting key proinflammatory cytokines and signaling pathways. In primary human keratinocytes stimulated with TPA, a Nanostring® nCounter gene expression assay demonstrated that HSP90 inhibition with RGRN-305 suppressed many proinflammatory genes. We next demonstrated that topical RGRN-305 application significantly ameliorated TPA-induced skin inflammation in mice. The increase in ear thickness was significantly reduced (up to 89% inhibition). In accordance, RNA sequencing and RT-qPCR revealed that RGRN-305 mitigated TPA-induced alterations in gene expression and suppressed genes implicated in inflammation. Furthermore, we discovered that the anti-inflammatory effects were mediated, at least partly, by suppressing the activity of NF-κB, ERK1/2, p38 MAPK and c-Jun signaling pathways. Our findings suggest that HSP90 inhibition may be a novel mechanism of action for treating immune-mediated skin disease beyond psoriasis, and it may be a topical treatment option.